PRODUCTION OF LETTUCE CHANGES IN RESPONSE TO THE USE OF MAGNETICALLY TREATED WATER - Pradela, V. A.; Yoshida, C. H. P.; Santos, D. C.; Santos, R. C.; Lapaz, A. M. (Revista Brasileira de Engenharia de Biossistemas, 2018)
In recent years, there has been a growing scientific research on innovation and agricultural technology regarding the action of the magnetic field under the germination and development of plants. In view of the above, this research had the objective of evaluating the initial development of lettuce (Lactuca Sativa L.) seedlings with conventional and magnetized water. The experiment was carried out in trays of 120 cells, the plot consisting of 12 cells with 10 replicates, where the treatments were treated magnetically and untreated. Weekly measurements of shoot length were taken and when the seedlings reached 24 days after sprouting, they were removed from the trays and the following parameters were evaluated: shoot length, shoot dry mass, root length and root dry mass. In the exposure time and magnetizing strength conditions, the use of magnetized water is beneficial for lettuce and probably for other crops. In particular, for lettuce, the results show that irrigation with magnetically treated water is efficient to obtain lettuce seedlings with higher biomass volume in shoot and root.